2022
DOI: 10.3389/fsoil.2022.838497
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Influence of Fertility and Rotation on Soil Nitrification Potential and Nitrifier Communities

Abstract: The agricultural imprints on soil microbial processes manifest at various timescales, leaving many temporal patterns to present slowly. Unfortunately, the lack of long-term continuous agricultural field sites in North America has left gaps in our understanding of agricultural management on biogeochemical processes and their controlling microbiota. Nitrification, ammonium oxidation by bacteria and archaea, is a critical control point in terrestrial nitrogen fluxes by oxidizing cationic ammonium to anionic nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 121 publications
(140 reference statements)
1
3
1
Order By: Relevance
“…The difference to agitated soil slurries was that NEO S and ammonium chloride had almost identical nitri cation rates. This con rms the hypothesis that ammonium accessibility is not solely responsible for active nitri er communities (Raglin et al, 2022).…”
Section: Discussionsupporting
confidence: 85%
“…The difference to agitated soil slurries was that NEO S and ammonium chloride had almost identical nitri cation rates. This con rms the hypothesis that ammonium accessibility is not solely responsible for active nitri er communities (Raglin et al, 2022).…”
Section: Discussionsupporting
confidence: 85%
“…However, our initial expectation of observing distinct potential nitri cation rates between fertilized and unfertilized soil, as indicated by similar studies (Mohanty et al, 2022;Raglin et al, 2022;Wang et al, 2018), was not observed in our experiments. This discrepancy could be attributed to the relatively short two-year treatment period or the possibility that nitri cation potentials are sustained through nitrogen mining from the relatively high soil organic matter (SOM) content in the non-fertilized treatment.…”
Section: Minimal Long-term Fertilization Effects In the Eldcontrasting
confidence: 48%
“…In addition to xed ammonium, clay minerals can sorb complex N-containing compounds, which can subsequently be mineralized to NH 4 + upon release (Nieder et al, 2011). While we did not speci cally study the taxonomic composition of the underlying nitri er communities, other studies have reported on functional redundancy among different taxonomic groups of nitri ers as a potential reason for the lack of a fertilizer-speci c response in eld soils (Gu et al, 2017;Raglin et al, 2022;Wu et al, 2011).…”
Section: Minimal Long-term Fertilization Effects In the Eldmentioning
confidence: 93%
“…These data indicate that rotation reduced soil denitrification, as well as NO and N 2 O emissions, thereby reducing the loss of nitrogen from the soil. Moreover, rotation enhanced soil ammonification, nitrification, and nitrogen fixation, in addition to increasing soil NO 3 − -N and NH 4 + -N content [30][31][32].…”
Section: Molecular Ecological Network Structurementioning
confidence: 96%